Lithium adsorption microsphere particles, and preparation method and application thereof
Patent Information
- Application Number
- CN202611163535.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-16
AI Technical Summary
但现有锂离子印迹材料多以商业化PVDF平板膜为基底,经表面化学修饰接枝印迹层,吸附容量逐步提升,但均受限于二维表面负载瓶颈,基膜孔结构固定不可控,印迹位点难以在三维空间高效负载,且膜形态易污染、再生困难、难以适配固定床等工业化吸附工艺
[0028] Beneficial effects: The key to this invention lies in first preparing polyvinylidene fluoride (PVDF) microspheres using a suspension-phase inversion method. The porous structure of the PVDF microspheres provides a three-dimensional loading platform with a high specific surface area for the lithium-ion imprinted layer. Then, through the adhesion effect of polydopamine oxidized by sodium periodate, lithium-ion imprinted polymers are loaded on the surface and within the pores of the PVDF microspheres. The resulting lithium adsorption microsphere particles have a three-dimensional imprinted structure, which is beneficial to improving the density of effective lithium adsorption recognition sites, thereby significantly improving the adsorption mass transfer efficiency and lithium adsorption capacity. At the same time, the lithium adsorption microsphere particles have a regular morphology and high mechanical strength, and can be directly used in fixed beds/adsorption towers, overcoming the application defects of membrane modules and powdered adsorbents, and are more suitable for industrial process applications.
Smart Images

Figure CN122912822A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of adsorption functional materials technology, specifically relating to a lithium adsorption microsphere particle, its preparation method, and its application. Background Technology
[0002] Currently, commonly used lithium recovery technologies include precipitation, solvent extraction, electrolysis, and adsorption. However, due to the similar chemical properties of magnesium and lithium, these processes are less effective in high-Mg environments. 2+ / Li + Significant shortcomings exist in complex systems. Precipitation methods involve adding carbonates or phosphates to precipitate Li. + Fixed as Li2CO3, the operation is simple and low-cost; however, under high magnesium-to-lithium ratio conditions, Mg... 2+ Co-precipitation is severe, with lithium loss often exceeding 20%, and subsequent purification processes are lengthy and involve high acid and alkali consumption. Solvent extraction can address this by designing the functional groups of the extractant to interact with Li. + Formation of stable complexes, thereby preferentially releasing Li in high magnesium-to-lithium ratio brines. + The lithium is transferred to an organic phase and back-extracted to obtain a lithium-rich solution. However, this process is lengthy, yields a single product, and requires significant equipment investment. Furthermore, traditional organic extractants are highly toxic and volatile, while ionic liquids, though environmentally friendly, are prohibitively expensive. Leaks in ecologically fragile areas like the Qinghai-Tibet Plateau can cause long-term pollution. These drawbacks collectively restrict their large-scale application. Therefore, developing highly selective, green, and low-consumption novel lithium recovery technologies has become a core scientific challenge in the field of lithium extraction from salt lakes and waste batteries.
[0003] Membrane separation technology is considered a promising and environmentally friendly separation technology, showing great potential in the extraction and purification of key metals such as lithium, cobalt, and nickel. To further enhance the selective recognition capability of membrane separation technology for specific ions, ion-imprinting technology (IIT) has been introduced into the preparation of membrane materials. The preparation of lithium-ion imprinted membranes mainly relies on five core elements: template ion, functional monomer, cross-linker, initiator, and eluent. However, existing lithium-ion imprinted materials mostly use commercial PVDF flat sheet membranes as substrates, with surface chemical modification and grafting of imprinted layers, gradually increasing adsorption capacity. However, these methods are limited by the two-dimensional surface loading bottleneck; the pore structure of the base membrane is fixed and uncontrollable, imprinted sites are difficult to load efficiently in three-dimensional space, and the membrane morphology is prone to fouling, regeneration is difficult, and it is difficult to adapt to industrial adsorption processes such as fixed beds. Therefore, developing a molded particulate adsorbent with high lithium adsorption capacity is of significant practical importance. Summary of the Invention
[0004] One of the objectives of this invention is to provide a method for preparing lithium adsorbent microspheres to overcome the above-mentioned problems.
[0005] The second objective of this invention is to provide lithium-adsorbed microspheres prepared by the above method.
[0006] A third objective of this invention is to provide the application of the lithium adsorption microspheres in lithium extraction and separation.
[0007] The preparation method of the lithium adsorbent microspheres includes the following steps: S1. Prepare an aqueous solution of a pore-forming agent and a degassed polyvinylidene fluoride (PVDF) solution, respectively. Add the degassed PVDF solution dropwise into the pore-forming agent aqueous solution under stirring to carry out a curing reaction. After the reaction is completed, PVDF microspheres are obtained; S2. Mix the PVDF microspheres obtained in step S1 with dopamine hydrochloride and a buffer solution. Add sodium periodate to the mixture to carry out a modification reaction to obtain polydopamine-modified PVDF microspheres; S3. Lithium chloride, 12-crown ether-4, and organic solvent II are mixed to obtain solution A. The polydopamine-modified polyvinylidene fluoride microspheres obtained in step S2, solution A, and coordinating monomers are subjected to reflux treatment in the presence of a crosslinking agent and an initiator. After the reaction, the microspheres are acid-washed and dried to obtain lithium adsorbed microsphere particles. The organic solvent I used in the polyvinylidene fluoride solution is a solvent that can dissolve polyvinylidene fluoride and is miscible with water. The average particle size of the polyvinylidene fluoride microspheres is 0.5~1.5 mm, and the porosity is 60~85%. The coordinating monomer is methacrylic acid and / or acrylic acid.
[0008] In a preferred embodiment, the pore size of the polyvinylidene fluoride microspheres is 0.05~0.5μm.
[0009] In a preferred embodiment, the average particle size of the lithium adsorbent microspheres is 0.8~2.0 mm.
[0010] In a preferred embodiment, in step S1, the pore-forming agent is selected from at least one of polypyrrolidone, polyvinyl alcohol, and polyethylene glycol.
[0011] In a preferred embodiment, in step S1, the mass concentration of the pore-forming agent in the aqueous solution of the pore-forming agent is 0.5~2wt%.
[0012] In a preferred embodiment, in step S1, the mass concentration of polyvinylidene fluoride in the polyvinylidene fluoride solution is 10~15wt%.
[0013] In a preferred embodiment, in step S1, the organic solvent I is selected from at least one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, and dimethyl sulfoxide.
[0014] In a preferred embodiment, in step S1, the polyvinylidene fluoride solution is obtained by dissolving polyvinylidene fluoride powder in N,N-dimethylacetamide solvent by stirring.
[0015] In a preferred embodiment, the conditions for stirring and dissolving in step S1 include: a temperature of 60~80℃ and a time of 3~5h.
[0016] In a preferred embodiment, in step S1, the degassing treatment method is static degassing and / or vacuum degassing.
[0017] In a preferred embodiment, in step S1, the amount of polyvinylidene fluoride solution added is 0.05~0.1 mL / time.
[0018] In a preferred embodiment, in step S1, the curing and molding reaction takes 1 to 2 hours.
[0019] In a preferred embodiment, in step S2, the amount of dopamine hydrochloride used is 0.1~0.3g, with the polyvinylidene fluoride microspheres weighing 1g.
[0020] In a preferred embodiment, in step S2, the pH value of the buffer solution is 4.5 to 5.5.
[0021] In a preferred embodiment, in step S2, the buffer solution is a sodium acetate solution.
[0022] In a preferred embodiment, in step S2, the mass ratio of dopamine hydrochloride to sodium periodate is 1:(1.05~1.1).
[0023] In a preferred embodiment, in step S3, the mass ratio of the polydopamine-modified polyvinylidene fluoride microspheres to lithium chloride, 12-crown ether-4, and coordination monomer is 1 g : (0.3~0.6) g : (0.33~0.65) g : (0.2~0.41) g.
[0024] In a preferred embodiment, in step S3, the conditions for the condensation reflux treatment include: a temperature of 60~70℃ and a time of 20~30h.
[0025] In a preferred embodiment, in step S3, the organic solvent II is selected from at least one of methanol, ethanol, and acetonitrile.
[0026] In a preferred embodiment, in step S3, the crosslinking agent is ethylene glycol dimethacrylate.
[0027] In a preferred embodiment, in step S3, the initiator is azobisisobutyronitrile.
[0028] Beneficial effects: The key to this invention lies in first preparing polyvinylidene fluoride (PVDF) microspheres using a suspension-phase inversion method. The porous structure of the PVDF microspheres provides a three-dimensional loading platform with a high specific surface area for the lithium-ion imprinted layer. Then, through the adhesion effect of polydopamine oxidized by sodium periodate, lithium-ion imprinted polymers are loaded on the surface and within the pores of the PVDF microspheres. The resulting lithium adsorption microsphere particles have a three-dimensional imprinted structure, which is beneficial to improving the density of effective lithium adsorption recognition sites, thereby significantly improving the adsorption mass transfer efficiency and lithium adsorption capacity. At the same time, the lithium adsorption microsphere particles have a regular morphology and high mechanical strength, and can be directly used in fixed beds / adsorption towers, overcoming the application defects of membrane modules and powdered adsorbents, and are more suitable for industrial process applications. Attached Figure Description
[0029] Figure 1 This is the adsorption breakthrough curve of the lithium adsorbed microspheres prepared in Example 1. Detailed Implementation
[0030] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. Furthermore, unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present invention.
[0031] The method for preparing lithium adsorbent microspheres provided by the present invention includes the following steps: S1. Prepare an aqueous solution of pore-forming agent and a polyvinylidene fluoride solution that has been degassed. Add the degassed polyvinylidene fluoride solution dropwise into the aqueous solution of pore-forming agent under stirring to carry out a curing and molding reaction. After the reaction is completed, polyvinylidene fluoride microspheres (PVDF microspheres) are obtained. S2. The polyvinylidene fluoride microspheres obtained in step S1 are mixed with dopamine hydrochloride and a buffer solution. Sodium periodate is added to the mixture to carry out a modification reaction, and polydopamine-modified polyvinylidene fluoride microspheres are obtained. S3. Lithium chloride, 12-crown ether-4, and organic solvent are mixed to obtain solution A. The polydopamine-modified polyvinylidene fluoride microspheres obtained in step S2, solution A, and coordinating monomers are subjected to reflux treatment in the presence of crosslinking agent and initiator. After the reaction, the microspheres are acid washed and dried to obtain lithium adsorbed microsphere particles.
[0032] In this invention, the average particle size of the polyvinylidene fluoride (PVDF) microspheres is 0.5–1.5 mm, for example, 0.5 mm, 0.8 mm, 1 mm, 1.2 mm, 1.5 mm, or any value between them. The porosity of the PVDF microspheres is 60–85%, for example, 60%, 65%, 70%, 75%, 80%, 85%, or any value between them. At this porosity, the PVDF microspheres possess good mechanical strength and sufficient porous structure to support lithium-ion imprinted polymers, which is beneficial for preparing lithium-adsorbed microsphere particles with a three-dimensional imprinted structure, thereby improving adsorption mass transfer efficiency and lithium adsorption capacity.
[0033] Furthermore, the pore size of the polyvinylidene fluoride microspheres is preferably 0.05~0.5μm, such as 0.05μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm or any value between them.
[0034] In this invention, in step S1, the pore-forming agent is preferably selected from one or more of polypyrrolidone (PVP), polyvinyl alcohol (PVA), and polyethylene glycol (PEG). The mass concentration of the pore-forming agent in the aqueous solution is preferably 0.5~2wt%, for example, 0.5wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, or any value between them. Controlling the mass concentration of the pore-forming agent within the above-mentioned preferred range has the advantage of balancing the quality of microsphere formation and the performance of the pore structure. This is because this concentration effectively prevents droplet adhesion, ensures the sphericity of the microspheres, and forms interconnected pores through appropriate pore formation, avoiding the problems of skin densification and pore-forming agent residue caused by excessively high concentrations. This provides a better reaction interface and mass transfer conditions for subsequent polydopamine modification and crown ether grafting.
[0035] In this invention, in step S1, the organic solvent I in the polyvinylidene fluoride solution is primarily a solvent capable of dissolving polyvinylidene fluoride and being miscible with water. Specific examples include, but are not limited to, any one or more of N,N-dimethylacetamide (DMAC), N,N-dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), and dimethyl sulfoxide (DMSO). The preferred mass concentration of polyvinylidene fluoride in the polyvinylidene fluoride solution is 10-15 wt%, for example, 10 wt%, 10.5 wt%, 11 wt%, 11.5 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, or any value between these values. When the mass concentration of polyvinylidene fluoride (PVDF) in the PVDF solution is controlled within the above-mentioned preferred range, it has the advantage of balancing solution fluidity, droplet formation effect, and microsphere structural strength, and stably preparing PVDF microspheres with regular spherical shape and dense and uniform structure. The reason is that when the concentration is below 10 wt%, the solution viscosity is too low, the mechanical strength of the droplets is insufficient, and they are easily dispersed and elongated by the water flow after being dropped into the coagulation bath, making it difficult to form complete spheres, and the resulting microspheres have poor mechanical strength. When the concentration is above 15 wt%, the solution viscosity is too high, the fluidity becomes poor, the droplets are difficult to disperse uniformly, and problems such as adhesion and uneven particle size are likely to occur. At the same time, it will slow down the solvent exchange rate and cause internal structural defects in the microspheres. The concentration range of 10~15 wt% can ensure stable droplet formation and regular spherical shape, and also ensure that the phase transformation process proceeds smoothly, ultimately obtaining PVDF microspheres with uniform particle size and good mechanical properties.
[0036] In one specific embodiment, the polyvinylidene fluoride solution can be obtained by dissolving polyvinylidene fluoride powder in N,N-dimethylacetamide solvent by stirring. The preferred conditions for stirring and dissolving include: a temperature of 60-80°C, such as 60°C, 65°C, 70°C, 75°C, 80°C, or any value between therewith; and a time of 3-5 hours, such as 3 hours, 4 hours, 5 hours, or any value between therewith.
[0037] In this invention, the degassing treatment in step S1 can be static degassing and / or vacuum degassing. Preferably, the static degassing involves allowing the polyvinylidene fluoride solution to stand at 60-80°C for 12-36 hours.
[0038] In this invention, in step S1, the amount of polyvinylidene fluoride solution added is preferably 0.05~0.1 mL / time, for example 0.05 mL / time, 0.06 mL / time, 0.07 mL / time, 0.075 mL / time, 0.08 mL / time, 0.09 mL / time, 0.1 mL / time, or any value between them. Preferably, the polyvinylidene fluoride solution can be added using a syringe or dropper. More preferably, when adding the polyvinylidene fluoride solution, the solution outlet of the syringe or dropper is close to the surface of the pore-forming agent aqueous solution or extends 1~2 cm below the surface.
[0039] In this invention, in step S1, the stirring method used for the pore-forming agent aqueous solution in a stirred state can be mechanical stirring or magnetic stirring, preferably magnetic stirring. The purpose of stirring is to ensure that the N,N-dimethylacetamide (DMAC) in the droplets formed after the polyvinylidene fluoride solution is added to the pore-forming agent aqueous solution is fully displaced into the water, thereby causing the polyvinylidene fluoride to precipitate and solidify to form polyvinylidene fluoride microspheres. There is no particular limitation on the stirring speed; the main point is to ensure that the pore-forming agent aqueous solution forms a stable vortex. In a specific embodiment, when the volume of the pore-forming agent aqueous solution is 100 mL, the stirring speed is preferably 30~50 r / min, for example, 30 r / min, 35 r / min, 40 r / min, 45 r / min, 50 r / min, or any value between them.
[0040] In this invention, in step S1, the curing reaction time is preferably 1 to 2 hours, for example 1 hour, 1.5 hours, 2 hours or any value between them.
[0041] In this invention, in step S2, taking 1g of the polyvinylidene fluoride microspheres as the starting point, the amount of dopamine hydrochloride is preferably 0.1~0.3g, for example 0.1g, 0.12g, 0.15g, 0.18g, 0.2g, 0.22g, 0.25g, 0.28g, 0.3g or any value between them.
[0042] In this invention, in step S2, the pH value of the buffer solution is preferably 4.5 to 5.5, for example, 4.5, 4.8, 5, 5.2, 5.5, or any value between them. The buffer solution is preferably a sodium acetate solution.
[0043] In this invention, in step S2, the mass ratio of dopamine hydrochloride to sodium periodate is preferably 1:(1.05~1.1), for example 1:1.05, 1:1.07, 1:1.09, 1:1, 1:1.05, 1:1.1 or any ratio therebetween.
[0044] In this invention, in step S3, the preferred mass ratio of the polydopamine-modified polyvinylidene fluoride microspheres to lithium chloride, 12-crown ether-4, and coordination monomer is 1g : (0.3~0.6)g : (0.33~0.65)g : (0.2~0.41)g. Based on 1g of the polydopamine-modified polyvinylidene fluoride microspheres, the amount of lithium chloride is preferably 0.3~0.6g, for example 0.3g, 0.4g, 0.5g, 0.6g or any value between them; the amount of 12-crown ether-4 is preferably 0.33~0.65g, for example 0.33g, 0.35g, 0.38g, 0.4g, 0.45g, 0.5g, 0.55g, 0.6g, 0.65g or any value between them; the amount of the coordinating monomer is preferably 0.2~0.41g, for example 0.2g, 0.25g, 0.3g, 0.35g, 0.4g, 0.41g or any value between them.
[0045] In this invention, the mixing conditions of lithium chloride, 12-crown ether-4, and organic solvent in step S3 may include: stirring at room temperature; and a time of 1 to 3 hours, for example, 1 hour, 2 hours, 3 hours, or any value between them.
[0046] In this invention, the conditions for the condensation reflux treatment in step S3 preferably include: a temperature of 60~70℃, such as 60℃, 62℃, 65℃, 68℃, 70℃ or any value between them; and a time of 20~30h, such as 20h, 22h, 24h, 26h, 28h, 30h or any value between them.
[0047] In this invention, specific examples of the organic solvent II in step S3 include, but are not limited to, any one or more of methanol, ethanol, and acetonitrile.
[0048] In this invention, in step S3, the coordinating monomer is methacrylic acid (MAA) and / or acrylic acid (AA). The crosslinking agent is a compound that can polymerize with the coordinating monomer under the action of an initiator, and specific examples include, but are not limited to, any one or more of ethylene glycol dimethacrylate (EGDMA), trimethoxypropane trimethacrylate (TRIM), divinylbenzene (DVB), and N,N'-methylenebisacrylamide (MBA), with ethylene glycol dimethacrylate (EGDMA) being particularly preferred. The initiator can be any one of the thermal initiators, with azobisisobutyronitrile (AIBN) being particularly preferred.
[0049] Furthermore, based on 1g of the polydopamine-modified polyvinylidene fluoride microspheres, the amount of the coordinating monomer is preferably 0.2~0.4g, for example 0.2g, 0.25g, 0.3g, 0.35g, 0.4g or any value between them; the amount of the initiator is preferably 0.02~0.04g, for example 0.02g, 0.03g, 0.04g or any value between them.
[0050] In this invention, the average particle size of the lithium adsorbent microspheres is preferably 0.8~2.0 mm, for example 0.8 mm, 1 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2 mm or any value between them.
[0051] The present invention will be described in detail below through specific embodiments. These embodiments are intended to explain the invention and should not be construed as limiting it. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0052] Example 1 This embodiment illustrates the preparation of lithium-adsorbed microspheres, as detailed below: S1. Prepare a 1 wt% polyvinylpyrrolidone aqueous solution (K30, PVP aqueous solution); weigh 12 g of polyvinylidene fluoride powder (PVDF) and add it to 88 g of N,N-dimethylacetamide (DMAC) solvent, stir and dissolve in a 70℃ water bath for 4 h to obtain a 12 wt% polyvinylidene fluoride solution (PVDF / DMAC solution), and continue to stand in a 70℃ water bath for 24 h to complete degassing; take 100 mL of the above-prepared PVP aqueous solution and place it in a beaker, turn on the magnetic stirrer at 30 r / min to make the PVP aqueous solution (1 wt%) form a stable vortex in the beaker, and then use a syringe (specification) The degassed PVDF / DMAC solution (12 wt%) was slowly added dropwise to a stirred PVP aqueous solution (10 mL, 0.075 ± 0.025 mL / time). During addition, the syringe needle was kept close to the surface of the PVP aqueous solution. After addition, stirring was continued for 2 hours. The microspheres in the liquid phase were collected by filtration and washed with an ethanol / water mixture. After drying, polyvinylidene fluoride microspheres were obtained. The average particle size of the polyvinylidene fluoride microspheres was measured to be 1.2 mm, and the porosity was 72%.
[0053] S2. Dissolve 0.2g of dopamine hydrochloride in a sodium acetate solution with a pH of 5, then add 1g of the polyvinylidene fluoride microspheres obtained in step S1. After stirring and mixing for 5 minutes, add sodium periodate solution (containing 0.218g of sodium periodate) dropwise. Continue stirring the reaction after the addition is complete until the solution turns dark black. Filter and collect the microspheres in the liquid phase and wash with an ethanol / water mixture. After drying, polydopamine-modified polyvinylidene fluoride microspheres are obtained.
[0054] S3. Weigh 90 mL of anhydrous methanol into a three-necked conical flask, then add 0.3 g of lithium chloride (LiCl) and 0.3 g of 12-crown ether-4. Stir at room temperature (25 °C) for 2 h to obtain a homogeneous solution A. Then, weigh 1 g of the polydopamine-modified polyvinylidene fluoride microspheres obtained in step S2 and add them to solution A. Under nitrogen protection, continue to add 0.4 g of methacrylic acid (MAA), 0.3 g of ethylene glycol dimethacrylate (EGDMA), and 0.03 g of azobisisobutyronitrile (AIBN) to solution A. Seal the system and reflux at 65 °C for 24 h. Filter and collect the microspheres in the liquid phase and wash with 1 mol / L hydrochloric acid. Then wash with deionized water until neutral and dry to obtain lithium adsorbed microsphere particles (average particle size of 1 mm).
[0055] Example 2 This embodiment illustrates the preparation of lithium-adsorbed microspheres, as detailed below: S1. Prepare a 2wt% polyvinyl alcohol aqueous solution (Mw = 30000~50000 g / mol, PVA aqueous solution); weigh 10 g of polyvinylidene fluoride powder (PVDF) and add it to 90 g of N,N-dimethylacetamide (DMAC) solvent, stir and dissolve in a 70℃ water bath for 4 h to obtain a 10wt% polyvinylidene fluoride solution (PVDF / DMAC solution), and continue to stand in a 70℃ water bath for 24 h to complete degassing; take 100 mL of the above-prepared PVA aqueous solution and place it in a beaker, turn on the magnetic stirrer at 30 r / min to make the PVA aqueous solution (1wt%) form a stable vortex in the beaker, and then use a syringe (specification) The degassed PVDF / DMAC solution (10 wt%) was slowly added dropwise to a stirred PVA aqueous solution (10 mL syringe needle, 0.075 ± 0.025 mL / drop). After addition, stirring was continued for 2 hours. The microspheres in the liquid phase were collected by filtration and washed with an ethanol / water mixture. After drying, polyvinylidene fluoride microspheres were obtained. The average particle size of the obtained polyvinylidene fluoride microspheres was 0.5 mm, and the porosity was 62%.
[0056] S2. Dissolve 0.2g of dopamine hydrochloride in a sodium acetate solution with a pH of 5, then add 1g of the polyvinylidene fluoride microspheres obtained in step S1. After stirring and mixing for 5 minutes, add sodium periodate solution (containing 0.218g of sodium periodate) dropwise. Continue stirring the reaction after the addition is complete until the solution turns dark black. Filter and collect the microspheres in the liquid phase and wash with an ethanol / water mixture. After drying, polydopamine-modified polyvinylidene fluoride microspheres are obtained.
[0057] S3. Weigh 90 mL of anhydrous methanol into a three-necked conical flask, then add 0.5 g of lithium chloride (LiCl) and 0.5 g of 12-crown ether-4. Stir at room temperature (25 °C) for 2 h to obtain a homogeneous solution A. Then, weigh 1 g of the polydopamine-modified polyvinylidene fluoride microspheres obtained in step S2 and add them to solution A. Under nitrogen protection, continue to add 0.2 g of methacrylic acid (MAA), 0.3 g of ethylene glycol dimethacrylate (EGDMA), and 0.03 g of azobisisobutyronitrile (AIBN) to solution A. Seal the system and reflux at 65 °C for 24 h. Filter and collect the microspheres in the liquid phase and wash with 1 mol / L hydrochloric acid. Then wash with deionized water until neutral and dry to obtain lithium adsorbed microsphere particles (average particle size of 1 mm).
[0058] Example 3 This embodiment illustrates the preparation of lithium-adsorbed microspheres, as detailed below: S1. Prepare a 0.5 wt% polyvinylpyrrolidone aqueous solution (K30, PVP aqueous solution); weigh 15 g of polyvinylidene fluoride powder (PVDF) and add it to 85 g of N,N-dimethylacetamide (DMAC) solvent. Dissolve the solution by stirring in a 70°C water bath for 4 hours to obtain a 15 wt% polyvinylidene fluoride solution (PVDF / DMAC solution). Continue to let it stand in a 70°C water bath for 24 hours to complete degassing; take 100 mL of the PVP aqueous solution prepared above and place it in a beaker. Turn on the magnetic stirrer at 30 r / min to make the PVP aqueous solution (1 wt%) form a stable vortex in the beaker. At this time, use a syringe (specification) The degassed PVDF / DMAC solution (15 wt%) was slowly added dropwise to a stirred PVP aqueous solution (10 mL, 0.075 ± 0.025 mL / time). During addition, the syringe needle was kept close to the surface of the PVP aqueous solution. After addition, stirring was continued for 2 hours. The microspheres in the liquid phase were collected by filtration and washed with an ethanol / water mixture. After drying, polyvinylidene fluoride microspheres were obtained. The average particle size of the obtained polyvinylidene fluoride microspheres was 0.8 mm, and the porosity was 68%.
[0059] S2. Dissolve 0.2g of dopamine hydrochloride in a sodium acetate solution with a pH of 5, then add 1g of the polyvinylidene fluoride microspheres obtained in step S1. After stirring and mixing for 5 minutes, add sodium periodate solution (containing 0.218g of sodium periodate) dropwise. Continue stirring the reaction after the addition is complete until the solution turns dark black. Filter and collect the microspheres in the liquid phase and wash with an ethanol / water mixture. After drying, polydopamine-modified polyvinylidene fluoride microspheres are obtained.
[0060] S3. Weigh 90 mL of anhydrous methanol into a three-necked conical flask, then add 0.3 g of lithium chloride (LiCl) and 0.3 g of 12-crown ether-4. Stir at room temperature (25 °C) for 2 h to obtain a homogeneous solution A. Then, weigh 1 g of the polydopamine-modified polyvinylidene fluoride microspheres obtained in step S2 and add them to solution A. Under nitrogen protection, continue to add 0.3 g of methacrylic acid (MAA), 0.3 g of ethylene glycol dimethacrylate (EGDMA), and 0.03 g of azobisisobutyronitrile (AIBN) to solution A. Seal the system and reflux at 65 °C for 24 h. Filter and collect the microspheres in the liquid phase and wash with 1 mol / L hydrochloric acid. Then wash with deionized water until neutral and dry to obtain lithium adsorbed microsphere particles (average particle size of 1 mm).
[0061] Comparative Example 1 This comparative example illustrates the preparation of a reference lithium adsorbent microsphere, as detailed below: Lithium-adsorbed microspheres were prepared according to the method of Example 1, except that in step S1, the polyvinylidene fluoride solution (PVDF / DMAC solution) was not subjected to degassing treatment by standing in a water bath at 70°C for 24 hours. All other conditions were the same as in Example 1, thereby obtaining reference lithium-adsorbed microspheres (average particle size of 1 mm).
[0062] Comparative Example 2 This comparative example illustrates the preparation of a reference lithium adsorbent microsphere, as detailed below: Lithium-adsorbed microspheres were prepared according to the method of Example 1, except that in step S1, an equal volume of PVP aqueous solution was replaced with pure water. The resulting polyvinylidene fluoride microspheres had an average particle size of 0.8 mm and a porosity of 58%. All other conditions were the same as in Example 1, thereby preparing reference lithium-adsorbed microspheres (average particle size of 1 mm). Test case The lithium adsorbed microspheres prepared in the above examples and comparative examples were tested for their relevant properties according to the following methods. The specific test methods are as follows, and the structures obtained from the tests are shown in Table 1.
[0063] (1) Mechanical strength test of lithium adsorption microspheres: Lithium adsorption microspheres with a particle size of 1±0.5mm were selected as the test samples and subjected to multiple mechanical property tests after drying and cooling.
[0064] ① The compressive strength of the microspheres was determined using a particle strength tester. The microspheres were loaded at a constant speed of 0.5 N / s at room temperature. The critical crushing pressure of 10 parallel samples was counted and the average value was calculated (10 microspheres with intact appearance were selected as the test samples in each group).
[0065] ② The wear resistance was evaluated through an oscillation friction test. The samples were oscillated at 200 r / min for 2 hours, and then the particle breakage was statistically analyzed by sieving and weighing. The wear rate of 10 parallel samples was calculated and the average value was obtained (10 intact microspheres were selected as the test samples in each group). The wear rate (%) = m1 / m0*100, where m0 represents the total mass of microspheres before oscillation (g), and m1 represents the mass of broken fine powder obtained by sieving after oscillation (g). Note: The lower the wear rate value, the better the wear resistance of the microspheres.
[0066] ③ A continuous water circulation method was used to simulate actual operating conditions. The microspheres were rinsed at a flow rate of 150 mL / min for 4 hours. The particle integrity of 10 parallel samples under hydraulic impact was calculated and the average value was obtained (10 intact microspheres were selected from each group as the test samples). Particle integrity (%) = m2 / m0*100%, where m0 represents the total mass of microspheres (g) before the hydraulic impact test, and m2 represents the mass (g) of unbroken, intact spherical microspheres obtained after sieving following the water impact. Note: The higher the particle integrity value, the better the microspheres' resistance to hydraulic erosion and the better their long-term stability in industrial fixed bed operation.
[0067] (2) Adsorption capacity test of lithium adsorption microspheres: 1g of lithium adsorption microspheres were placed in 100mL of Li... + In a 200 mg / L solution (pH = 7.0, 25℃), samples were taken at 5-minute intervals to test the Li content. + The concentration and total adsorption time were 180 min. The adsorption breakthrough curve of the lithium-adsorbed microspheres prepared in Example 1 is shown below. Figure 1 As shown, the adsorption amount continued to increase from 0 to 120 min, and reached adsorption equilibrium at 180 min.
[0068] (3) Cyclic stability test of lithium adsorbed microspheres: The lithium adsorbed microspheres that were saturated with adsorption were eluted with 0.5 mol / L hydrochloric acid for 2 h, washed with deionized water until neutral, and the adsorption experiment of method (2) was repeated 5 times. The retention rate of the adsorption capacity of the 5th adsorption was calculated compared with the first adsorption capacity.
[0069] Table 1
[0070] As shown in Table 1, compared with the comparative example, the lithium adsorption microspheres provided in this embodiment of the invention not only have higher lithium adsorption capacity and better cycle stability, but also better mechanical strength. The compressive strength, wear rate and particle integrity under water impact are all better than those of the comparative example.
[0071] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention without departing from the principles and spirit of the present invention.
Claims
1. A method for preparing lithium adsorbent microspheres, characterized in that, The preparation method includes the following steps: S1. Prepare an aqueous solution of pore-forming agent and a polyvinylidene fluoride solution that has been degassed. Add the degassed polyvinylidene fluoride solution dropwise into the aqueous solution of pore-forming agent under stirring to carry out a curing and molding reaction. After the reaction is completed, polyvinylidene fluoride microspheres are obtained. S2. The polyvinylidene fluoride microspheres obtained in step S1 are mixed with dopamine hydrochloride and a buffer solution. Sodium periodate is added to the mixture to carry out a modification reaction, and polydopamine-modified polyvinylidene fluoride microspheres are obtained. S3. Lithium chloride, 12-crown ether-4, and organic solvent II are mixed to obtain solution A. The polydopamine-modified polyvinylidene fluoride microspheres obtained in step S2, solution A, and coordination monomer are subjected to reflux treatment in the presence of crosslinking agent and initiator. After the reaction, the microspheres are acid washed and dried to obtain lithium adsorbed microsphere particles. Wherein, the organic solvent I used in the polyvinylidene fluoride solution is a solvent that can dissolve polyvinylidene fluoride and is miscible with water; the average particle size of the polyvinylidene fluoride microspheres is 0.5~1.5 mm, and the porosity is 60~85%; the coordinating monomer is methacrylic acid and / or acrylic acid.
2. The method for preparing lithium adsorbent microspheres according to claim 1, characterized in that, The pore size of the polyvinylidene fluoride microspheres is 0.05~0.5μm; Preferably, the average particle size of the lithium adsorbent microspheres is 0.8~2.0 mm.
3. The method for preparing lithium adsorbent microspheres according to claim 1, characterized in that, In step S1, the pore-forming agent is selected from at least one of polypyrrolidone, polyvinyl alcohol, and polyethylene glycol; Preferably, the mass concentration of the pore-forming agent in the aqueous solution is 0.5~2wt%.
4. The method for preparing lithium adsorbent microspheres according to claim 1, characterized in that, In step S1, the mass concentration of polyvinylidene fluoride in the polyvinylidene fluoride solution is 10~15 wt%. Preferably, the polyvinylidene fluoride solution is obtained by dissolving polyvinylidene fluoride powder in organic solvent I by stirring. Preferably, the organic solvent I is selected from at least one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, and dimethyl sulfoxide; Preferably, the conditions for stirring and dissolving include: a temperature of 60~80℃ and a time of 3~5h; Preferably, the degassing treatment method is static degassing and / or vacuum degassing.
5. The method for preparing lithium adsorbent microspheres according to claim 1, characterized in that, In step S1, the amount of polyvinylidene fluoride solution added is 0.05~0.1 mL / time; Preferably, the curing and molding reaction time is 1-2 hours.
6. The method for preparing lithium adsorbent microspheres according to claim 1, characterized in that, In step S2, based on the weight of 1g of the polyvinylidene fluoride microspheres, the amount of dopamine hydrochloride used is 0.1~0.3g; Preferably, the pH value of the buffer solution is 4.5 to 5.5; Preferably, the buffer solution is a sodium acetate solution; Preferably, the mass ratio of dopamine hydrochloride to sodium periodate is 1:(1.05~1.1).
7. The method for preparing lithium adsorbent microspheres according to claim 1, characterized in that, In step S3, the mass ratio of the polydopamine-modified polyvinylidene fluoride microspheres to lithium chloride, 12-crown ether-4, and coordination monomer is 1g : (0.3~0.6)g : (0.33~0.65)g : (0.2~0.41)g. Preferably, the conditions for the condensation reflux treatment include: a temperature of 60~70℃ and a time of 20~30h.
8. The method for preparing lithium adsorbent microspheres according to claim 1, characterized in that, In step S3, the organic solvent is selected from at least one of methanol, ethanol, and acetonitrile; Preferably, the crosslinking agent is ethylene glycol dimethacrylate; Preferably, the initiator is azobisisobutyronitrile.
9. Lithium-adsorbed microspheres prepared by the method according to any one of claims 1 to 8.
10. The application of the lithium adsorption microspheres according to claim 9 in lithium extraction and separation.